Analisis Kepadatan Penghuni, Luas Lantai dan Luas Ventilasi Terhadap Suhu dan Kelembaban di Rumah Kos Putri Kajor, Nogotirto, Gamping, Sleman, DIY - Nur Hasanah; Achmad Husein; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Rooms in boarding houses should meet some health requirements, such as room’s width orsize, number of occupants, ventilation area, temperature and humidity, based on the set qualitystandards. This study was aimed to determine the effect of occupant density, floor area andventilation area on temperature and humidity in Putri Kajor boarding house located in Kajor, Nogotirto, Gamping, Sleman, by conducting a cross sectional designed survey. The number of therooms under study was 52. The density, floor area and ventilation were measured bu using rollmeter, meanwhile for temperature and humidity, thermohygrometer was used. Descriptively,the number of the rooms which fulfilled the requirement of occupant denisty was 5 (9,6 %), fulfilled the requirement of floor area was also 5 (9,6 %), fulfilled the requirement of ventilation area was 49 (94,2 %), fulfilled the requirement of room temperature was 52 (100 %), and nonefulfilled the requirement of humidity. The results of statistical analysis at 5 % significance levelconclude that occupant density, floor area and ventilation influence temperature of the rooms(p-value = 0,019), however, for room’s humidity the effect is not found (p-value = 0,513).